Experimental evaluation of rolling contact fatigue in railroad wheels. (October 2016) - Sciammarella, C.A.; Chen, R.J.S.; Gallo, P.; Berto, F.; Lamberti, L.
Graphical abstract: Highlights: Contact fatigue and surface damage in railroad wheels are very complex phenomena. An experimental approach to evaluate rolling contact fatigue is presented. Six different materials employed in rail wheel constructions have been considered. Laboratory conditions were successfully scaled to actual railroad conditions. Crack formation/propagation mechanisms have been analyzed on a statistical basis. Abstract: Surface damage in railroad wheels is a very complex phenomenon and the contact fatigue plays a fundamental role in the damage process. In the case of railroad wheels the actual fracture process is quite different from the conventional idea of fracture in a load bearing structural component. The cracks that are generated by contact fatigue are not the source of actual wheels cracking but lead to the damaging phenomenon called shelling which implies separation of chunks of material from the surface. Shelling is mainly due to the presence of a fluid in the contact area, which penetrates in the fatigue cracks and causes a crack propagation leading to the separation of a portion of the wheel surface. A basic starting point to analyze this phenomenon is to study the crack development in the contact surface and to evaluate the behavior of different types of steels used for wheels manufacturing. However, the challenge to obtain a reliable similitude between laboratory and real conditions is far from straightforward. The present paper illustrates an experimental approach for rolling contact fatigue and shelling evaluation based on the possibility of simulating, in the laboratory, boundary conditions that can be scaled to the actual railroad, thus providing a realistic evaluation of the contact fatigue life of different steels.